The Critical Discourse Analysis of Moral Values in a Senior High School English Textbook Published by Indonesian Ministry of Educational Culture - Hidayatullah, Ikmal; Setyono, Budi; Ariyanto, Sugeng (English Education Study Program, 2023)
The effect of globalization in all sectors of life will impact on the moral degradation of the Indonesian students. It is due to the fact that it is easy for students to imitate cultural behaviors from other countries through social media that are difficult to be controlled by parents and teachers. School children who are still immature in mind may easily adopt the fast spread of information from different parts of the world regardless of whether or not they are appropriate with the Indonesian culture. Culturally, what is considered good behaviors in one country may not be accepted in other countries or vice versa. Therefore, the inclusion of moral education (character education) in Indonesia is crucial to avoid students’ misconception of moral values and to direct students’ behaviors in appropriate ways.